Relatório de Estágio Profissional "DOCÊNCIA - O CONFRONTO COM A REALIDADE" - Jorge Miguel Neto Amorim (2018)
The Professional Internship appears in the Second Cycle in Teaching Physical Education on Basic and Secondary school of the Faculty of Sports Sciences of the University of Porto, this study does present an Internship report that portrays the experiences of a trainee teacher during a school year. The headquarters was the Secondary School of Ermesinde, belonging to the Ermesinde School Grouping. All this process was supervised by two teachers, one of the Secondary School of Ermesinde and a Teacher from the FADEUP. This Internship Report is divided into nine chapters, the first to (1) Introduction, the second (2) Personal Area, where my career was developed, my academic career and my knowledge and expectations regarding Professional Internship, the third (3) Institutional Area, where the school's framework appears, as well as the characterization of the students and the Internship Center, the fourth (4) Professional Practice Area where the whole Plan and conception is presented, Aspects of (5) Participation in School and Community Relations, in which the most outstanding moments are presented during the year, such as the realized tournaments and the cut-off, mato, the sixth (6) Case of exercise for personal evolution, it is not what form regular physical exercise regular students, the seventh (7) Conclusions on the theme presented on document, the eighth (8) chapter is in Bibliographical References and finally the ninth (9) corresponds to the Annexes.